A wholistic program for the well-being of selected elderly women in Quezon City - Mills, Amparo Gaston (2005)
This study was conducted to determine how elderly persons, particularly women, are coping with aging, and if and how the quality of their lives may be improved. Towards this end, a wholistic program was developed to measure the elderly persons' level of well-being in the three dimensions, namely, econo-physical, phyco-social, and moral-spiritual, and, corollarily, draw a psycho-graphic profile. This study focused on a group of elderly women belonging to a community in Quezon City. Of the 48 respondents, 26 were chosen to undergo the wholistic program. This consisted of 11 sessions with ten lessons and one focused group discussion. However, for purposes of comparison, all 48 respondents were given researcher-developed pre-test and post-test questionnaires. Based on statistical tools used, i.e., descriptive statistics, Wilcoxon Signed Ranks Test, and Mann-Whitney Test, significantly higher scores were noted for the 26 participants, as compared with those for non-participants. This was evident in the psycho-graphic profile (i.e., attitude towards life, life changes adjustment and community service), as well as in the three dimensions of well-being. A focused group discussion confirmed these findings. This study demonstrated how the wholistic program significantly improved the well-being of the participants. The results of the study indicate the need to develop a wholistic program for the elderly, so that they may prove to society and, more importantly, to themselves, that aging is not a hindrance to living a full and productive life.